2017
DOI: 10.2196/mental.5537
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction Through the Phase of Adolescence: A Questionnaire Study

Abstract: BackgroundAdolescents increasingly use the Internet for communication, education, entertainment, and other purposes in varying degrees. Given their vulnerable age, they may be prone to Internet addiction.ObjectiveOur aim was to identify possible differences in the purpose of Internet use among adolescents with respect to age subgroup, country of residence, and gender and the distribution of Internet addiction across age subgroups. Another aim was to determine if there is a correlation between the purpose of In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
63
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 15 publications
14
63
1
4
Order By: Relevance
“…Similar to previous cross-sectional studies, males presented with higher IA symptom severity at both 16 and 18 years (although the difference was not statistically significant at 16 years) (Shi et al, 2017;Karacic & Oreskovic, 2017;Ostovar et al, 2016;Anderson et al, 2016;Chen et al, 2015;Choo et al, 2015;Gentile et al, 2011;Haagsma et al, 2013;Hong et al, 2014;Willoughby, 2008;Yu & Shek, 2013;Stavropoulos et al, 2013aStavropoulos et al, , 2013bYen et al, 2009;Shaw & Black, 2008;Johansson & Götestam, 2004).…”
Section: Gender Differences In Understanding Prevention and Treatmensupporting
confidence: 83%
See 3 more Smart Citations
“…Similar to previous cross-sectional studies, males presented with higher IA symptom severity at both 16 and 18 years (although the difference was not statistically significant at 16 years) (Shi et al, 2017;Karacic & Oreskovic, 2017;Ostovar et al, 2016;Anderson et al, 2016;Chen et al, 2015;Choo et al, 2015;Gentile et al, 2011;Haagsma et al, 2013;Hong et al, 2014;Willoughby, 2008;Yu & Shek, 2013;Stavropoulos et al, 2013aStavropoulos et al, , 2013bYen et al, 2009;Shaw & Black, 2008;Johansson & Götestam, 2004).…”
Section: Gender Differences In Understanding Prevention and Treatmensupporting
confidence: 83%
“…Less developed social skills, higher relationship avoidance, and less communicative responses to stress in males (in the context of everyday interaction) may enhance the likelihood of excesive online socialization in males compared with females over time, and thus potentially maintaining higher levels of IA symptoms (Del Giudice, 2011). To our knowledge, although a higher IA risk for males has been shown repeatedly in cross-sectional studies, the present finding is perhaps the first to clarify the nature of IA gender differences longitudinally (Shi et al, 2017;Karacic & Oreskovic, 2017;Ostovar et al, 2016;Anderson et al, 2016;Chen et al, 2015;Choo et al, 2015;Gentile et al, 2011;Haagsma et al, 2013;Hong et al, 2014;Willoughby, 2008;Yu & Shek, 2013;Stavropoulos et al, 2013aStavropoulos et al, , 2013bYen et al, 2009;Shaw & Black, 2008;Johansson & Götestam, 2004). …”
Section: Gender Differences In Understanding Prevention and Treatmensupporting
confidence: 61%
See 2 more Smart Citations
“…They used internet for school/work (20.2%) and entertainment (11.9%). [31] Other study done by Miao (2017) [32] found that Social networking, school work, entertainment, gaming and shopping ranked as the top five among all the online activities. According to literature, values used as reference points to characterize long electronic devices use time varies between 2 and 5 hours/day.…”
Section: Discussionmentioning
confidence: 94%